Nano-titanium dioxide composite whitening self-cleaning concrete material, and preparation method and application thereof
Patent Information
- Application Number
- CN202610980062.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-02
- Publication Date
- 2026-10-27
AI Technical Summary
其一,团聚分散难题未彻底攻克,常规分散手段无法实现纳米颗粒单分散,需大幅提升TiO2掺量才能达到预期自清洁效果,显著抬高原料成本;其二,光催化活性依赖紫外光,可见光响应弱,阴面、阴天环境下自清洁能力大幅衰减,自然光利用效率偏低;其三,功能耐久性不足,内掺样品内部TiO2无法接触光照仅起填充作用,表层有效光催化组分有限;涂覆型涂层与基体粘结力差,车轮摩擦、雨水冲刷、冻融循环后易剥落失效;其四,高掺量纳米TiO2易干扰水泥正常水化,延缓凝结、降低抗压强度,难以平衡自清洁性能与结构力学指标
本发明提供了一种纳米TiO2复合增白自清洁混凝土材料,该混凝土材料装饰性能优异、自清洁效率高、结构性能优秀、长期稳定性好、生产成本低。具体来说,白水泥基体与SiO2、TiO2多重增白组分协同,白度远高于普通混凝土,且自清洁功能可长期维持表面洁净,避免积灰泛黄,装饰耐久性显著提升;N掺杂实现可见光响应,核壳结构保障活性位点有效暴露,自然光下可高效降解表面有机污染物,同时光致超亲水效应配合雨水冲刷实现自清洁,适配户外实际应用场景;纳米SiO2优化水泥石与界面结构,配合减水剂保证工作性,混凝土力学强度、抗渗性等指标满足工程要求,实现功能-结构一体化;核壳化学键结合、界面过渡区致密化共同保障功能组分不易脱落,光催化性能与增白效果在长期服役中衰减慢,使用寿命长;以SiO2替代部分TiO2降低原料成本,工艺过程无需特殊设备,适配现有混凝土生产流程,便于规模化推广。
Smart Images

Figure FT_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of building materials technology, specifically relating to a nano-titanium dioxide composite whitening self-cleaning concrete material, its preparation method, and its application. Background Technology
[0002] Concrete facades of urban buildings and municipal roads are often contaminated by atmospheric dust, organic oil, and nitrogen oxides, resulting in blackening and aging of the finish and high maintenance and cleaning costs. Nano-TiO2-modified cementitious materials with photocatalytic self-cleaning capabilities have become a research hotspot in green building materials. Nano-TiO2, with its non-toxic, chemically stable, and UV-excited photocatalytic oxidation properties, can decompose surface organic pollutants and achieve long-term self-cleaning through super-hydrophilic rainwater rinsing. It also refines the pores of cement hydration products and improves the matrix's impermeability and mechanical properties, making it a core modifying filler for multifunctional concrete. However, the extremely small particle size, huge specific surface area, and extremely high surface energy of nano-TiO2 pose a serious agglomeration problem in high-alkali, calcium-rich cement paste systems. Agglomerated particles not only significantly reduce the effective photocatalytic reaction area and weaken self-cleaning efficiency but also create pore defects within the concrete, deteriorating its strength and durability. Simple ultrasonic or water-reducing agent dispersion can only temporarily break up agglomerates; secondary agglomeration easily occurs during mixing and hydration, hindering the large-scale application of nano-TiO2 in cement-based systems.
[0003] The mainstream technical approaches for TiO2 self-cleaning concrete are mainly divided into two categories: internal admixture modification and surface coating. The internal admixture method involves directly incorporating the powder into the mixture, which can achieve overall photocatalytic function. Research focuses on TiO2 dosage, crystal form screening, and compounding of composite mineral admixtures. The surface coating method involves spraying or impregnating a TiO2 coating onto the surface of the component, which has a higher utilization rate of photocatalytic materials and is mostly used for the renovation of existing buildings.
[0004] However, existing nano-TiO2 self-cleaning concrete still faces several key technological bottlenecks, preventing its widespread engineering application. Firstly, the problem of agglomeration and dispersion has not been completely overcome. Conventional dispersion methods cannot achieve single-particle dispersion of nanoparticles, requiring a significant increase in TiO2 content to achieve the desired self-cleaning effect, thus significantly raising raw material costs. Secondly, photocatalytic activity depends on ultraviolet light, with weak visible light response. Self-cleaning ability is significantly reduced in shaded or overcast conditions, resulting in low natural light utilization efficiency. Thirdly, functional durability is insufficient. In internally incorporated samples, the TiO2 cannot be exposed to light and only serves a filling function, limiting the effective photocatalytic components on the surface. Coatings have poor adhesion to the substrate, easily peeling off and failing after wheel friction, rain erosion, and freeze-thaw cycles. Fourthly, high nano-TiO2 content can interfere with normal cement hydration, delaying setting and reducing compressive strength, making it difficult to balance self-cleaning performance and structural mechanical properties. These performance shortcomings, light utilization defects, and the contradiction between durability and mechanical synergy stemming from particle agglomeration are the core technological pain points that urgently need to be addressed in the current field of self-cleaning concrete. Summary of the Invention
[0005] This invention aims to solve at least one of the technical problems existing in the prior art. To this end, this invention proposes a nano-TiO2 composite whitening self-cleaning concrete material, in which core-shell structured SiO2@N-TiO2 is added. This SiO2 acts as a photocatalyst, imparting self-cleaning function to the concrete, while the SiO2 core acts as a nanofiller, utilizing its pozzolanic activity to react with cement hydration products, simultaneously improving the mechanical properties and durability of the concrete. Through the design of the composite admixture, multiple functions such as self-cleaning, reinforcement, and even self-repair can be integrated into one, making it a truly integrated "structure-function" building material.
[0006] This invention also proposes a method for preparing the above-mentioned nano-TiO2 composite whitening self-cleaning concrete material.
[0007] This invention also proposes the application of the above-mentioned nano-TiO2 composite whitening self-cleaning concrete material.
[0008] According to a first aspect of the present invention, a nano-TiO2 composite whitening self-cleaning concrete material is provided, wherein the raw materials of the nano-TiO2 composite whitening self-cleaning concrete material include: a composite functional admixture, cement and aggregate; the composite functional admixture includes core-shell particles, nano-SiO2 particles and a water-reducing agent; the core-shell particles have SiO2 as the core and TiO2 as the shell.
[0009] In some embodiments of the present invention, the TiO2 shell in the core-shell particles is nitrogen-doped modified TiO2.
[0010] In some embodiments of the present invention, the core size of the core-shell particle is 150-250 nm.
[0011] In some embodiments of the present invention, the shell thickness of the core-shell particle is 5-15 nm.
[0012] In some embodiments of the present invention, the aggregate includes coarse aggregate and fine aggregate.
[0013] In some embodiments of the present invention, the coarse aggregate comprises crushed stone with a diameter of 5-25 mm.
[0014] In some embodiments of the present invention, the fine aggregate comprises medium sand.
[0015] In some embodiments of the present invention, the cement includes at least one of ordinary silicate cement and white silicate cement.
[0016] In some embodiments of the present invention, the water-reducing agent includes a polycarboxylate water-reducing agent.
[0017] According to a second aspect of the present invention, a method for preparing the nano-TiO2 composite whitening self-cleaning concrete material described in the first aspect of the present invention is provided, the preparation method comprising the following steps: S1: Mix nano-SiO2 particles and titanium source to react, then add nitrogen source to react, collect solid phase for drying and calcination, grind calcined product to obtain core-shell particles; S2: Mix the core-shell particles, nano-SiO2 particles and water-reducing agent obtained in step S1 to obtain a composite functional additive; S3: Mix the composite functional admixture, cement, aggregate and water obtained in step S2 to obtain nano-TiO2 composite whitening self-cleaning concrete material.
[0018] In some embodiments of the present invention, the titanium source in step S1 includes tetrabutyl titanate.
[0019] In some embodiments of the present invention, the nitrogen source in step S1 includes dicyandiamide.
[0020] In some embodiments of the present invention, the weight ratio of the nano-SiO2 particles and the titanium source in step S1 is 1:(1-3).
[0021] In some embodiments of the present invention, the reaction time of the nano-SiO2 particles and the titanium source in step S1 is 3-5 h.
[0022] In some embodiments of the present invention, the weight ratio of the nano-SiO2 particles to the nitrogen source in step S1 is (40-60):3.
[0023] In some embodiments of the present invention, the reaction time for adding the nitrogen source in step S1 is 0.5-2 h.
[0024] In some embodiments of the present invention, the calcination temperature in step S1 is 350°C-450°C.
[0025] In some embodiments of the present invention, the calcination time in step S1 is 1-3 h.
[0026] In some embodiments of the present invention, the calcination in step S1 is preceded by a drying treatment, the temperature of which is 70°C-90°C and the time of which is 20-40 min.
[0027] In some embodiments of the present invention, the weight ratio of the core-shell particles, nano-SiO2 particles and water-reducing agent in step S2 is (2-6):(1-2)(1-2).
[0028] In some embodiments of the present invention, the weight ratio of the composite functional admixture, cement, aggregate and water in step S3 is 1:(8-11):(40-50):(4-5).
[0029] According to a third aspect of the present invention, the application of the nano-TiO2 composite whitening self-cleaning concrete material described in the first aspect of the present invention or the nano-TiO2 composite whitening self-cleaning concrete material prepared by the preparation method described in the second aspect of the present invention in the preparation of self-cleaning materials is proposed.
[0030] The present invention has at least the following beneficial effects: This invention provides a nano-TiO2 composite whitening self-cleaning concrete material, which exhibits excellent decorative properties, high self-cleaning efficiency, superior structural performance, good long-term stability, and low production cost. Specifically, the white cement matrix synergistically combines SiO2 and TiO2 whitening components, resulting in a whiteness far exceeding that of ordinary concrete. Its self-cleaning function maintains surface cleanliness for a long time, preventing dust accumulation and yellowing, and significantly improving decorative durability. Nitrogen doping enables visible light response, and the core-shell structure ensures effective exposure of active sites, allowing for efficient degradation of surface organic pollutants under natural light. Simultaneously, the photo-induced superhydrophilic effect, combined with rainwater rinsing, achieves self-cleaning, making it suitable for practical outdoor applications. Nano-SiO2 optimizes the cement stone and interface structure, and, in conjunction with water-reducing agents, ensures workability. The concrete's mechanical strength, impermeability, and other indicators meet engineering requirements, achieving functional-structural integration. Core-shell chemical bonding and densification of the interface transition zone jointly ensure that functional components are not easily detached. The photocatalytic performance and whitening effect decay slowly during long-term service, resulting in a long service life. Replacing part of TiO2 with SiO2 reduces raw material costs, the process requires no special equipment, is compatible with existing concrete production processes, and facilitates large-scale promotion. Attached Figure Description
[0031] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein: Figure 1 This is a graph showing the detection results of the degradation rate of organic dyes in the experimental examples of this invention. Detailed Implementation
[0032] The following will describe the concept and technical effects of the present invention clearly and completely with reference to embodiments, so as to fully understand the purpose, features and effects of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are all within the scope of protection of the present invention.
[0033] All ingredient parts mentioned in the following examples refer to parts by weight.
[0034] Example 1 This embodiment provides a nano-TiO2 composite whitening and self-cleaning concrete material, the preparation method of which is as follows: 1) Preparation of modified core-shell composite particles (SiO2@N-TiO2): Ten parts of nano-SiO2 particles were added to 100 parts of anhydrous ethanol and ultrasonically dispersed for 30 min. Then, 30 parts of tetrabutyl titanate aqueous solution (a mixture of 20 parts tetrabutyl titanate and 5 parts deionized water) were slowly added dropwise, ensuring the entire mixture was added within 1 h. The reaction was stirred at room temperature for 4 h. 0.6 parts of dicyandiamide were added to the reaction system, and the reaction was stirred for another 1 h. The solid phase was collected by filtration and dried in an 80℃ oven for 30 min. Finally, it was placed in a muffle furnace and heated to 400℃ at a rate of 7℃ / min. It was calcined at 400℃ for 2 h, cooled, and then ground to obtain the modified core-shell composite particles SiO2@N-TiO2. The core size of the SiO2@N-TiO2 core-shell particles was 200 nm, and the shell thickness was 10 nm.
[0035] 2) Compound formulation of composite functional admixtures: Mix 60 parts of SiO2@N-TiO2 core-shell particles prepared in step 1), 15 parts of nano-SiO2 particles and 15 parts of polycarboxylate superplasticizer powder in a V-type mixer for 30 min until homogeneous to obtain a composite functional additive.
[0036] 3) Preparation of nano-TiO2 composite whitening self-cleaning concrete material: 175 parts water, 650 parts medium sand, and 1150 parts crushed stone (5-25 mm in diameter) were poured into a mixing pot and stirred at 140 rpm for 30 seconds. Then, 380 parts white silicate cement PW42.5 and 40 parts of the composite functional admixture prepared in step 2) were added to the mixing pot and stirred at 140 rpm for 4 minutes to obtain a mixture. The mixture was poured into a mold and compacted by vibration. The nano-TiO2 composite whitening self-cleaning concrete material was obtained by curing under standard conditions (temperature 20±2℃, humidity ≥95%) for 28 days.
[0037] Example 2 This embodiment provides a concrete material whose preparation method differs from that of Embodiment 1 only in that steps 1) and 2) are omitted and SiO2@N-TiO2 core-shell particles are not added. All other steps are consistent with those of Embodiment 1.
[0038] Example 3 This embodiment provides a nano-TiO2 composite whitening self-cleaning concrete material. The only difference between its preparation method and that of Embodiment 1 is that the nano-SiO2 particles in step 2) are omitted, while the remaining steps are consistent with those of Embodiment 1.
[0039] Example 4 This embodiment provides a nano-TiO2 composite whitening self-cleaning concrete material. The only difference between this material and the preparation method in Example 1 is that the polycarboxylate superplasticizer in step 2) is omitted, while the rest of the steps are consistent with those in Example 1.
[0040] Example 5 This embodiment provides a concrete material whose preparation method differs from that of Embodiment 1 only in that steps 1) and 2) are omitted and no composite functional admixture is added in step 3). All other steps are consistent with those of Embodiment 1.
[0041] Example 6 This embodiment provides a nano-TiO2 composite whitening self-cleaning concrete material. The only difference between this material and the preparation method in Example 1 is that the composite functional admixture in step 3) is replaced with an equal amount of SiO2@N-TiO2 core-shell particles. All other steps are the same as in Example 1.
[0042] Example 7 This embodiment provides a concrete material whose preparation method differs from that of Embodiment 1 only in that the composite functional admixture in step 3) is replaced with an equal amount of nano-SiO2 particles, while the remaining steps are consistent with those of Embodiment 1.
[0043] Example 8 This embodiment provides a concrete material whose preparation method differs from that of Embodiment 1 only in that the composite functional admixture in step 3) is replaced with an equal amount of polycarboxylate superplasticizer, while the remaining steps are consistent with those of Embodiment 1.
[0044] Example 9 This embodiment provides a nano-TiO2 composite whitening self-cleaning concrete material. The only difference between its preparation method and that of Embodiment 1 is that the calcination treatment in step 1) is omitted, while the remaining steps are consistent with those of Embodiment 1.
[0045] Example 10 This embodiment provides a nano-TiO2 composite whitening and self-cleaning concrete material, the preparation method of which is as follows: 1) Preparation of modified core-shell composite particles (TiO2@SiO2): Ten parts of nano-TiO2 were added to 100 parts of an ethanol-water solution (anhydrous ethanol:deionized water = 4:1) and ultrasonically dispersed for 30 min. The pH of the solution was adjusted to 9-10 using concentrated ammonia, and then 15 parts of an ethanol solution of tetrabutyl orthosilicate (a mixture of 10 parts tetrabutyl titanate and 5 parts anhydrous ethanol) were slowly added dropwise, ensuring the entire addition was completed within 1 h. The reaction was stirred at room temperature for 4 h. The solid phase was collected by filtration and dried in an oven at 80 °C for 12 h to obtain modified core-shell composite particles TiO2@SiO2. The core size of these TiO2@SiO2 core-shell particles was 200 nm, and the shell thickness was 10 nm.
[0046] 2) Compounding of composite functional additives: consistent with Example 1.
[0047] 3) Preparation of nano-TiO2 composite whitening self-cleaning concrete material: consistent with Example 1.
[0048] Example 11 This embodiment provides a nano-TiO2 composite whitening self-cleaning concrete material. The only difference between its preparation method and that of Embodiment 1 is that the SiO2@N-TiO2 core-shell particles in step 2) are replaced with nano-TiO2 with an equal molar amount of Ti and nano-SiO2 with an equal molar amount of Si. All other steps are consistent with those of Embodiment 1.
[0049] Test case This experiment tested the comprehensive performance of the concrete materials provided in Examples 1-11. The specific experimental methods and results are as follows: 1. Degradation rate of organic dyes Test principle: Photocatalytic reaction is used to degrade organic dyes on the surface, and the photocatalytic efficiency is quantified by color change.
[0050] Test method: Rhodamine B (RhB) was used as the contaminant. A 0.01 mmol / L RhB solution was uniformly sprayed onto the surface of concrete specimens (5 cm × 5 cm) prepared according to the methods provided in Examples 1-11, and dried at room temperature in the dark for 10 min. The specimens were then placed under ultraviolet light (UVA, wavelength 365 nm, intensity 10 W / m²). 2 Under irradiation, the surface absorbance was recorded at different time intervals (0, 1, 2, 4, 8 h) using a UV spectrophotometer. The absorbance was converted into the concentration of organic dye using a standard curve, and the degradation rate at the corresponding time points was calculated. Degradation rate (%) = (C0) / (C0) C) / C0 × 100%, where C0 is the initial dye concentration and C is the residual concentration after a certain period of illumination. The result is as follows: Figure 1 As shown.
[0051] Depend on Figure 1 The results show that the degradation of organic dyes by the nano-TiO2 composite whitening self-cleaning concrete material provided by this invention is time-dependent. Example 1 uses the sol-gel method to prepare SiO2@N-TiO2 core-shell composite particles, with high-whiteness nano-SiO2 as the core and TiO2 loaded, which solves the problems of TiO2 agglomeration and encapsulation deactivation, and extends the photoresponse to the visible light region through N doping, simultaneously achieving whitening efficiency and cost reduction. It achieved a degradation rate of 92% after 8 hours. Example 2, lacking the crucial SiO2@N-TiO2 core-shell particles, exhibits a significantly reduced self-cleaning ability compared to Example 1; Example 3: Due to the lack of SiO2, the SiO2 protective layer is missing. N-TiO2 is prone to phase change or active sites being covered in the cement hydration environment, which ultimately leads to a decrease in photocatalytic performance. Example 4: Due to the lack of water-reducing agent, the core-shell particles may be unevenly dispersed in the cement paste, resulting in local agglomeration and a slight decrease in self-cleaning effect; Example 5 lacks the entire composite functional admixture, which is the core component of self-cleaning. Its omission directly affects the self-cleaning performance of the concrete material, with a degradation rate of only 5% after 8 hours. Examples 6, 7, and 8 all retain only a single component in the composite functional admixture. The SiO2@N-TiO2 core-shell composite particles, SiO2, and polycarboxylate superplasticizer work synergistically. The performance of concrete materials will decrease after omitting two components. In Example 9, due to the lack of a calcination step, TiO2 failed to form a highly catalytically active anatase crystal form and was easily transformed into a rutile phase with lower photocatalytic activity at high temperatures, ultimately affecting the photocatalytic effect. Example 10 reversed the order of the core-shell structure, which reduced the exposure of active sites of TiO2. Part of the TiO2 surface was covered by a SiO2 shell, and the active sites were blocked, resulting in a decrease in photocatalytic efficiency. In Example 11, the SiO2@N-TiO2 core-shell composite particles were replaced with independent nano-SiO2 and nano-TiO2 particles introduced into the system. Since the two were not prepared as a core-shell structure, the nano-TiO2 was easily deactivated by hydration products, resulting in a decrease in photocatalytic efficiency.
[0052] 2. Water absorption rate Water absorption rate can be used to evaluate the waterproofing performance and pore structure changes of concrete surfaces. The water absorption rate of the concrete materials provided in Examples 1-11 was tested, and the capillary water absorption rate was characterized by the amount of water collected per unit area per unit time. The results are shown in Table 1.
[0053] Table 1 Water Absorption Rate
[0054] As shown in Table 1, due to the lack of SiO2, the water absorption rate of Examples 3, 5, 6, and 8 increased significantly, indicating that their porosity was much higher than that of Example 1. This is because SiO2 reacts with the cement hydration product Ca(OH)2. )2 A volcanic ash reaction occurs, forming CSH gel. This reaction can reduce the porosity of concrete.
[0055] 3. Whiteness The white pigment properties of nano-TiO2 impart a whitening effect to concrete, and the whiteness increases with the increase of TiO2 content. The whiteness of the concrete materials provided in Examples 1-11 was tested using a whiteness meter according to the national standard GB / T 5950-2008, and the results are shown in Table 2.
[0056] Table 2 Whiteness
[0057] As shown in Table 2, the lack of TiO2 will lead to a decrease in the whiteness of concrete materials.
[0058] 4. Compressive strength The compressive strength of the concrete materials provided in Examples 1-11 was tested according to the method provided in GB / T 50081-2019, and the results are shown in Table 3.
[0059] Table 3 Compressive Strength
[0060] As shown in Table 3, the mechanical properties of Examples 3, 5, 6, and 8 are significantly reduced due to the lack of SiO2. This is because nano-SiO2 particles can increase the density of cement, fill the interfacial transition zone between aggregate and cement paste, reduce interfacial porosity, weaken the orientation of Ca(OH)2, and improve interfacial bond strength and concrete impermeability. However, Example 9, lacking a calcination step, has a significantly increased porosity compared to Example 1, resulting in a decrease in its compressive strength.
[0061] The embodiments of the present invention have been described in detail above. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention. Furthermore, unless otherwise specified, the embodiments of the present invention and the features thereof can be combined with each other.
Claims
1. A nano-TiO2 composite whitening self-cleaning concrete material, characterized in that, The raw materials of the nano-TiO2 composite whitening self-cleaning concrete material include: composite functional admixtures, cement and aggregates; the composite functional admixtures include core-shell particles, nano-SiO2 particles and water-reducing agents; the core-shell particles have SiO2 as the core and TiO2 as the shell.
2. The nano-TiO2 composite whitening self-cleaning concrete material according to claim 1, characterized in that, The TiO2 shell in the core-shell particles is made of nitrogen-doped modified TiO2.
3. The nano-TiO2 composite whitening self-cleaning concrete material according to claim 1, characterized in that, The core-shell particle has a core size of 150-250 nm; Preferably, the shell thickness of the core-shell particle is 5-15 nm.
4. The nano-TiO2 composite whitening self-cleaning concrete material according to claim 1, characterized in that, The aggregates include coarse aggregates and fine aggregates; Preferably, the cement includes at least one of ordinary Portland cement and white Portland cement; Preferably, the water-reducing agent includes a polycarboxylate water-reducing agent.
5. The method for preparing the nano-TiO2 composite whitening self-cleaning concrete material according to any one of claims 1-4, characterized in that, The preparation method includes the following steps: S1: Mix nano-SiO2 particles and titanium source to react, then add nitrogen source to react, collect solid phase for drying and calcination, grind calcined product to obtain core-shell particles; S2: Mix the core-shell particles, nano-SiO2 particles and water-reducing agent obtained in step S1 to obtain a composite functional additive; S3: Mix the composite functional admixture, cement, aggregate and water obtained in step S2 to obtain nano-TiO2 composite whitening self-cleaning concrete material.
6. The preparation method according to claim 5, characterized in that, The titanium source mentioned in step S1 includes tetrabutyl titanate; Preferably, the nitrogen source in step S1 includes dicyandiamide.
7. The preparation method according to claim 5, characterized in that, The weight ratio of the nano-SiO2 particles and the titanium source in step S1 is 1:(1-3). Preferably, the weight ratio of the nano-SiO2 particles to the nitrogen source in step S1 is (40-60):
3.
8. The preparation method according to claim 5, characterized in that, The calcination temperature in step S1 is 350℃-450℃; Preferably, the calcination time in step S1 is 1-3 h.
9. The preparation method according to claim 5, characterized in that, The weight ratio of the core-shell particles, nano-SiO2 particles and water-reducing agent in step S2 is (2-6):(1-2)(1-2); Preferably, the weight ratio of the composite functional admixture, cement, aggregate and water in step S3 is 1:(8-11):(40-50):(4-5).
10. The application of the nano-TiO2 composite whitening self-cleaning concrete material according to any one of claims 1-4 or the nano-TiO2 composite whitening self-cleaning concrete material prepared by any one of claims 5-9 in the preparation of self-cleaning materials.